A web application to calculate the mass defect and nuclear binding energy per nucleon. (November 2022) - Paraschiv, Lizica Simona; Paraschiv, Spiru; Dragan, Marcel
Abstract: The discovery of radioactivity proved that the energy stored in the nucleus could be released as radioactive particles' kinetic energy. Fission and fusion reactions generate enormous amounts of energy that could be used to generate electricity in nuclear power plants. The energy released or absorbed in these nuclear reactions comes from the different binding energies associated with each nucleus. Nuclear binding energy is the amount of energy required to keep a nucleus's protons and neutrons together, and nuclear power is the amount of energy released during nuclear fission or fusion. Each type of nucleus has its own binding energy, which is the amount of energy lost when its nuclei came together and are the same as the amount of energy needed to split them. The paper describes a web application for computing nuclear binding energy per nucleon. The calculation of nuclear binding energy in terms of MeV/ nucleon entails determining the mass defect and converting the mass defect into energy per nucleon.